Efectos de la adición de suero de queso deshidratado en dietas de lechones destetados a los 30 días de edad (Veterinary Science, 2017)
The objective of this work was to evaluate the efficacy of supplemented dried whey (DW) (20%) in a corn-soybean heat processed (SHP)-based diet for 30 days weaned pig's performance. A total of 128 piglets (9.034 +- 2.025 kg) were allotted by litter and weight to two groups: Control (corn-SHP) and Treatment (corn-SHP-DW). The experimental groups were formed by 4 pens of 16 piglets each one. All piglets were weighted at weaning, at 14 days and 28 days post-weaning, for calculating daily weight gain in both periods. Feed intake and feed: gain ratios were also determined. DW addition improved feed intake (673.8 +- 33.3 vs 770.3 +- 42.8 g/day) and weight gain (363.4 +- 3.2 vs 420.2 +- 10.9 g/day) during the first period but not during the second period post-weaning. Feed: gain ratio was not affected by DW in any period. In conclusion, supplementation of DW to starter diets during 2 weeks after 30 days weaning improves the piglets' performance
Keywords: Weanling pigs